EMPLOYEE OPINIONS TOWARDS HUMAN RESOURCE DEVELOPMENT OF THE RIGHT AND LIBERTIES PROTECTION DEPARTMENT, MINISTRY OF JUSTICE - Chanwarin, Nisachon; Hemaphan, Pornphan (Journal of Humanities and Social Sciences, Rajapruk University, 2024)
The objectives of this study are 1) to study the level of employee opinions towards human resource development by using a case study of the Rights and Liberties Protection Department, 2) to compare employee opinions towards human resource development, classified by personal and perceptual factors, and 3) to provide suggestions for laying out a framework for human resource development in the organization in the future. The samples are 187 employees, working at the Rights and Liberties Protection Department in 2022. The data was collected by questionnaires and statistics were analyzed by using Statistical Package for the Social Sciences. The descriptive statistics were presented in percentage, mean, and standard deviation. Furthermore, the inferential statistics were employed for hypothesis testing; one-Way ANOVA, and Fisher’s Least Significance Difference (LSD) test were used for comparison method. The result showed that the level of employee opinions towards human resource development of the Rights and Liberties Protection Department was at a moderate level ( = 2.83 , S.D. = 1.16). The hypothesis testing found that there was a significant difference in the employee opinions in human resource development among personal factors, composed of age, work experience, and education level, at the .05 level of statistical significance. On contrary, there was no significant difference among personal factors--gender, type of position, and affiliation, including factors with regard to perception of the Rights and Liberties Protection Department’s human resource development at the .05 level of statistical significance.